Getting One's Ducks in a Row: Conservation Units of Common Eiders (Somateria mollissima) Throughout North America - Turner, Russell (2019)
Anthropogenic climate change is resulting in a variety of consequences for ecosystems and biodiversity. Collectively these changes are negatively impacting species survival and are increasing rates of extinction. Species can, however, adjust to environmental changes through range shifts, phenotypic plasticity, or genetic adaptation. To ensure successful species conservation in the face of climate change, it is now crucial that a species’ capacity for such change, as well as existing evolutionary differences among populations, are incorporated into species’ management plans. This is particularly important for species dependent on Arctic conditions because climate change will disproportionately affect these regions. Here, I evaluate the spatial genetic structure of a highly mobile Arctic breeding sea duck, the Common Eider (Somateria mollissima) by analyzing double-digest restriction site-associated DNA sequencing (ddRAD-seq) data from 320 ducks originating from 24 breeding populations spread across North America. I identify two evolutionarily significant units that show a clear west-east divide, which is suggestive of two distinct glacial refugia. I also identify five to six genetically distinct management units and detect five potentially adaptive units within North America. I also identify a pattern of isolation-by-distance across my entire study area and within the Eastern evolutionary significant unit. However, a similar pattern was not evident within the Western evolutionary significant unit. Taken together, my results reveal biologically important population genetic structure that must be considered for the successful long-term management of the eider. My thesis contributes to the growing body of literature aimed at better understanding the broad spectrum of genetic differentiation observed in avian populations that inhabit the Arctic, which will help better manage their conservation. M.Sc.